Stabilization and control of tie-line power flow of microgrid including wind generation by distributed energy storage - Molina, Marcelo Gustavo (2010)
High penetration of wind generation in electrical microgrids causes fluctuations of tie-line power flow and significantly affects the power system operation. This can lead to severe problems, such as system frequency oscillations, and/or violations of power lines capability. With proper control, a distribution static synchronous compensator (DSTATCOM) integrated with superconducting magnetic energy storage (SMES) is able to significantly enhance the dynamic security of the power system. This paper proposes the use of a SMES system in combination with a DSTATCOM as effective distributed energy storage (DES) for stabilization and control of the tie-line power flow of microgrids incorporating wind generation. A new detailed model of the integrated DSTATCOM-SMES device is derived and a novel three-level control scheme is designed. The dynamic performance of the proposed control schemes is fully validated using MATLAB/Simulink. © 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.